Frequency of cognitive impairment in older forensic inpatients: results of a pilot cross-sectional study. Issue 1 (2nd January 2023) - Verhülsdonk, S.; Folkerts, A.K.; Hufnagel, S.; Bohn, C.; Hoeft, B.; Supprian, T.; Kalbe, E.
ABSTRACT: The number of older inpatients in forensic hospitals is growing. Overall, complex needs in treatment are identified for this group, and differ significantly from those of younger forensic patients. To date, there has been little awareness of the relevance of age-related changes in cognitive function of older forensic patients. Data on the prevalence of cognitive disorders in older forensic inpatients are rare, and, for German forensic hospitals, completely lacking. Against this background, a pilot project was conducted in forensic departments of five Psychiatric hospitals in North Rhine Westphalia, Germany. Sociodemographics, crime-related characteristics and medical data of inpatients aged 60 years and older were collected. Established cognitive screening instruments were administered. 34 of 134 forensic patients aged 60–91 years participated in the study. Dependent on the instrument used, up to 65% showed impairment in global cognitive functioning and up to 68% showed executive dysfunctions. Our pilot data indicate that cognitive impairment in older forensic patients in Germany is more frequent than reported for the older general population in Germany. Based on the findings, the extent to which diagnostic routines should be implemented and the complex factors (e.g. the underlying mental illness) that need to be taken into account are discussed.